Literatur Review: Intervensi Keperawatan Untuk Meningkatkan Kebahagiaan Lansia - Mare, Agustina Chriswinda Bura; Maryuti, Ira Ayu; Sukmawati, Ermalynda (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2024)
Happiness includes positive feelings and positive activities. Unhappiness that occurs in the elderly can affect the health, welfare and quality of life of the elderly. The aim of this research is to determine nursing interventions that can increase the happiness of the elderly. Literature searches used electronic databases, namely EBSCO-host, science direct, and google scholar. The literature search was limited to articles published in the last 10 years (2014-2024), in English, with full text access, and the type of article was review and research article. The keywords used in the literature search were nursing intervention and elder happiness. The results of the literature search found 4 articles that met the inclusion and exclusion criteria. There are four nursing interventions that can be carried out to increase the happiness of the elderly, namely national music activities, painting therapy, narrative reminiscence therapy, and humour therapy. Nurses are expected to be able to carry out the above interventions to increase the happiness of the elderly.